National Strategic Projects: Yogyakarta-Bawen Toll Road Development Policy from the Perspective of Agile Governance (Center for Public Policy and Digital Government Universitas Muhammadiyah Yogyakarta, 2024)
Referring to the Yogyakarta-Bawen toll road development policy, specifically Notification Letter Number 593/9965/2020 concerning the Yogyakarta-Bawen Toll Road Development Plan in the Special Region of Yogyakarta. Furthermore, Yogyakarta Governor Decree Number 405/KEP/2022 concerning amending the Decree of the Governor of the Special Region of Yogyakarta Number 385/KEP/2020 concerning the Determination of the Location of the Yogyakarta-Bawen Toll Road Development in the Special Region of Yogyakarta. Various governors' decisions in the policy of making the Yogyakarta-Bawen toll road have undergone various changes. This is to design and produce good policy formulation. Formulation in design policies is important because policy formulation can affect the success and impact of the Yogyakarta-Bawen Toll Road project. With the various stages, it is hoped that a good policy will emerge considering that there are directions and goals to be achieved in the construction of the Yogyakarta-Bawen toll road, which is certainly for the prosperity of the people. The agenda-setting stage of the process is carried out by processing the public problem into a policy problem. In the stage of referring to the case study taken, the reasons prompting the formulation of the Yogyakarta-Bawen Toll Road development policy are diverse.